2012
DOI: 10.15376/biores.7.4.5677-5690
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rattan Filler Loadings on Properties of Rattan Powder-Filled Polypropylene Composites

Abstract: This study investigates the effects of filler loading on the properties of rattan powder-filled polypropylene composites. The composites were prepared by incorporating rattan powder of average size 180 µm into polypropylene matrix using a Polydrive Thermo Haake internal mixer. Filler loadings of the rattan powders ranged between 0 and 40 parts per hundred parts of resin (phr). Mechanical, morphological, and thermal properties were studied. The tensile strength, elongation at tensile failure, and impact strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
2
2
1
Order By: Relevance
“…Another factor could be poor interfacial adhesion due to differences in polarities between the polar agrowaste filler and nonpolar LDPE matrix which could initiate and propagate sites for failures. Similar observations have also been reported in our previous work [23] and by other researchers using natural fillers [11,[24][25][26][27][28][29]. The addition of MAPE improved the tensile strength when compared with the corresponding PHF/LDPE composites.…”
Section: Resultssupporting
confidence: 90%
“…Another factor could be poor interfacial adhesion due to differences in polarities between the polar agrowaste filler and nonpolar LDPE matrix which could initiate and propagate sites for failures. Similar observations have also been reported in our previous work [23] and by other researchers using natural fillers [11,[24][25][26][27][28][29]. The addition of MAPE improved the tensile strength when compared with the corresponding PHF/LDPE composites.…”
Section: Resultssupporting
confidence: 90%
“…This is due to the dispersive resistance from ESP filler particles which increases the resistance to the flow of PVC especially at a high filler content. This trend was also observed in a study by Othman et al [20] and Shaari Balakrishnan et al [21]. On the other hand, the processing torque of PVC/ESP composite at a particle size of 0.2 µm exhibits lower stabilisation torque compared to that at a particle size of 7 µm.…”
Section: Resultssupporting
confidence: 83%
“…The finding is contrary with the previous studies, who found incorporation of kenaf fibers had improved strength properties of the composites [26,27]. This scenario suggesting that poor interfacial bonding occurred between hydrophilic fillers and hydrophobic matrix, even though compatibilizers were applied [28]. On the other hand, the tensile strength of PP decreased significantly to 37.82 MPa after addition of 30 wt % lignin.…”
Section: Discussioncontrasting
confidence: 85%